Adaptability and yield stability of common bean genotypes - Duarte, João Batista; Zimmermann, Maria José de O. (Pesquisa Agropecuaria Brasileira, 1994)
This research was proposed to evaluate the behaviour of grain yield of 76 genotypes of bean (Phaseolus vulgaris L.) of cream seed (mulatinho) color, tested in twelve Brazilian environments (1984/85 and 1985/86). The statistic procedure used was the bisegmented linear regression. Twenty five percent of the genotypes responded differently under favourable or unfavourable environmental conditions. Among these genotypes, some responded better to environmental improvements in favourable conditions and others responded better to favourable conditions. These behaviours indicated that the first genotypes showed adaptation to environments of low to average yield potential while the others showed to be adapted to average to high yielding environments. The other 75% of genotypes showed the same pattern of response in better environmental conditions as in those poor ones. Among these genotypes, three types of adaptative response were observed: genotypes adapted to low yielding (poor) environments; genotypes with general adaptability, and other ones with adaptation to high yielding (rich) environments. For each type of adaptative response, the genotypes of more stable behaviour and higher yield were indicated. The evaluated germplasm showed also low yield potential for an advanced cropping condition.